EXPLORING THE IMPACT OF FINANCIAL LITERACY ON THE ECONOMIC EMPOWERMENT OF TRIBAL WOMEN IN TIRUVALLUR, TAMIL NADU - N. Ramalakshmi; S. Umamageswari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In today’s digital age, financial literacy plays a key role in helping individuals manage their finances and improve their quality of life. This study examines the relationship between financial literacy and the economic empowerment of tribal women in Tiruvallur district, Tamil Nadu. The research utilizes an exploratory and descriptive approach, combining both qualitative and quantitative methods. The study focuses on tribal women engaged in income-generating activities, either through entrepreneurship or employment. A sample of 150 participants was selected using convenience sampling, and data was collected through structured questionnaires. Descriptive and inferential statistical techniques were used to analyse the data. The research specifically investigates the impact of various components of financial literacy, including savings and investments, banking products and services, financial planning and budgeting, and financial security. The results reveal a strong positive correlation between financial literacy and economic empowerment, with "Savings and Investments" emerging as the most significant predictor of economic empowerment. Banking products and financial planning also play a significant role, although to a lesser extent. Financial security, however, showed a weaker influence on economic empowerment. The findings highlight the importance of improving financial literacy among tribal women, particularly in areas such as savings and investments, which can enhance their economic opportunities and decision-making power. By increasing financial literacy, women can gain the knowledge needed to make informed financial decisions, ultimately boosting their financial independence and well-being. This study contributes to understanding how financial literacy can empower marginalized groups like tribal women. It offers valuable insights for policymakers and practitioners working to improve financial inclusion and empowerment. However, the study’s limitations include its regional focus and sample size, suggesting the need for further research in other regions or with larger, more diverse samples to gain a broader understanding of financial literacy’s impact on women’s empowerment.